Development of screening instrument and manual for children with Asperger Syndrome (ISSAKKM / SIMCAS) - Abd Hamid, Siti Rafiah; Saad, Supiah; Ismail, Nik Ahmad Hisham; Ismail, Khamsiah; Nik Abdul Rahman, Nik Suryani; Ibrahim, Haniz (Universiti Pendidikan Sultan Idris, 2019)
Children with Asperger syndrome (high-functioning autism spectrum disorder) develop into adulthood along diverse paths, and some often experience problems in school or occupational settings despite their high intellectual or language abilities. Better quality of life was associated with factors such as suitable medication, mother’s support and early diagnosis, while poorer quality of life was associated with the presence of aggressive behaviors. In line with the development of special education programmes for children with special needs, early detection of asperger syndrome cases could help the ECCE program provider to cater for early intervention program for children with asperger syndrome. Early intervention serves as a meaningful starting point in providing an appropriate program for children with asperger syndrome.